2013
DOI: 10.1016/j.compositesa.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

X-ray microtomography analysis of the damage micromechanisms in 3D woven composites under low-velocity impact

Abstract: ABSTRACT3D woven composites reinforced with either S2 glass, carbon or a hybrid combination of both and containing either polyethylene or carbon z-yarns were tested under low-velocity impact. Different impact energies (in the range of 21-316 J) were used and the mechanical response (in terms of the impact strength and energy dissipated) was compared with that measured in high-performance, albeit standard, 2D laminates. It was found that the impact strength in both 2D and 3D materials was mainly dependent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 22 publications
1
59
0
Order By: Relevance
“…However, this is outside the scope of this review, which is concerned solely with the improvement in damage resistance and tolerance due to the thermoplastic toughening phase. Information on the use of these types of fabrics, and their effect on impact tolerance can be found in references [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, this is outside the scope of this review, which is concerned solely with the improvement in damage resistance and tolerance due to the thermoplastic toughening phase. Information on the use of these types of fabrics, and their effect on impact tolerance can be found in references [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the response of the laminated composites, the effect of the through-thickness binder was significant as it supressed the delamination. An interesting study by Seltzer et al (Seltzer et al 2013) revealed the damage mechanisms of 3D S2-glass, carbon and hybrid woven composites by X-ray Computed Tomography (CT) due to low-velocity impact. In addition, they compared the energy absorption of the 3D woven composites with that of 2D laminated counterparts.…”
Section: Impact/indentation Testingmentioning
confidence: 99%
“…As the main advantage of 3D woven composites is clearly their out-of-plane enhanced properties, many researchers for example (Ji et al 2007;Luo et al 2007;Hao et al 2008;Walter et al 2009;Gerlach et al 2012;Seltzer et al 2013;Umer et al 2016) studied the effect of the z-binding yarns on the impact damage behaviour and the energy absorption of those material systems. Impact testing in literature was classified based on the impact velocity to low (< 10 m/s) as reported in (Umer et al 2016), high (~20 to 50 m/s) as in (Ji et al 2007;Hao et al 2008) and ballistic (~900 m/s) as discussed in (Walter et al 2009).…”
Section: Impact/indentation Testingmentioning
confidence: 99%
“…The size of the representative volume for tomography was chosen as a compromise among several factors: the resolution (the smaller the sample the higher the achievable resolution) for the detection of the smallest pores, the detection of a sufficiently large number of pores for statistical relevance and a sufficiently large specimen volume to contain the largest pores in the samples. In addition, the damage introduced by low-velocity impact in the laminates was studied by means of XCT, as in previous studies [14,15].…”
Section: X-ray Computed Microtomographymentioning
confidence: 99%